Comparison of Immuno-PET of CD138 and PET imaging with (64)CuCl(2) and (18)F-FDG in a preclinical syngeneic model of multiple myeloma - Bailly, Clément (Oncotarget, 2018)
PURPOSE: Although recent data from the literature suggest that PET imaging with [18]-Fluorodeoxyglucose ((18)F-FDG) is a promising technique in multiple myeloma (MM), the development of other radiopharmaceuticals seems relevant. CD138 is currently used as a standard marker in many laboratories for the identification and purification of myeloma cells, and could be used in phenotype tumor imaging. In this study, we evaluated a (64)Cu-labeled anti-CD138 murine antibody ((64)Cu-TE2A-9E7.4) and a metabolic tracer ((64)CuCl(2)) for PET imaging in a MM syngeneic mouse model. EXPERIMENTAL DESIGN AND RESULTS: (64)Cu-TE2A-9E7.4 antibody and (64)CuCl2 were evaluated via PET imaging and biodistribution studies in C57BL / KaLwRij mice bearing either 5T33-MM subcutaneous tumors or bone lesions. These results were compared to 18F-FDG-PET imaging. Autoradiography and histology of representative tumors were secondly conducted. In biodistribution and PET studies, (64)Cu-TE2A-9E7.4 displayed good tumor uptake of subcutaneous and intra-medullary lesions, greater than that demonstrated with (18)F-FDG-PET. In control experiments, only low-level, non-specific uptake of (64)Cu-labeled isotype IgG was observed in tumors. Similarly, low activity concentrations of (64)CuCl(2) were accumulated in MM lesions. Histopathologic analysis of the immuno-PET–positive lesions revealed the presence of plasma cell infiltrates within the bone marrow. CONCLUSIONS: (64)Cu-labeled anti-CD138 antibody can detect subcutaneous MM tumors and bone marrow lesions with high sensitivity, outperforming (18)F-FDG-PET and (64)CuCl(2) in this preclinical model. These data support (64)Cu-anti-CD138 antibody as a specific and promising new imaging radiopharmaceutical agent in MM.